WAYS TO USE INTERACTIVE TECHNIQUES IN MUSIC LESSONS - Jalilov, F.A. (Journal of Higher Education and Academic Advancement, 2024)
In this article, there are opinions about the methods of using pedagogical technologies in schools, the methods, methods and means of using interactive methods to increase the effectiveness of lessons in music education